Kinerja Pelayanan PDAM Tirta Moedal di Perumnas Banyumanik, Kota Semarang - I Dewa Gede Dwi Permana Putra; Mardwi Rahdriawan (Jurusan Perencanaan Wilayah dan Kota, 2020)
As a public service, it needs to be done through PDAM Tirta Moedal, Semarang City in carrying out its tasks in Performance is a record of that result from the function of a particular job or activity over a certain period of time. While the measurement is as a method to improve / agreed results compared to predetermined goals. Based on the above understanding can be agreed above. Improve work achievements or achievements obtained from the organization within the framework of achieving the goals and objectives that have been determined and agreed upon together within a certain period of time. Five dimensions have been chosen which have been developed into 25 variables in PDAM services.One that relates to the supply of clean water is that which is carried out by PDAM Tirta Moedal, Semarang City in the service area of the southern branch which is related to clean water services. The quality of clean and dirty water is changed, the continuity of clean water that stops at certain times until the clean air discharge is turned on once every 2 days in several places. This also happened to the Banyumanik Perumnas in the service area of the southern branch of the Tirta Moedal PDAM. This housing is one of the longest-established housing estates in the city of Semarang specifically in the south. It is interesting to know how to improve the performance of PDAM Tirta Moedal Semarang City in the Banyumanik Housing, obtaining information from customers using needs analysis and gap analysis. In the interest-performance analysis the suitability level (Tki) corresponds to the position of 70.02% and is included in the satisfied category in 28 variables which become the focus of research. while in the gap analysis / resolved at a value of -1.31 which means that it is included in the service category not good when compared performance with importance.